Effects of a neuromodulation protocol associated with sports training on upper limb function in a high-performance para-athlete: a case report - Aleixo, G. F.; Oliveira, L. S.; Fernandes, L. F. R. M.; Luvizutto, G. J.; Lobato, D. F. M. (Research in Sports Medicine, 2026)
This study investigated whether transcranial direct current stimulation (tDCS) optimizes the upper limb functional performance in a para-athlete with spinal cord injury (SCI). A right-handed para-athlete specializing in shotput, discus, and javelin throw with an incomplete SCI participated. The tDCS was applied in the left primary motor cortex twice-weekly for 5 weeks (20 min/session), associated with sport-specific training. Shoulder medial (MR) and lateral rotators (LR) isometric torque, handgrip and key pinch strength, and the specific functional performance were evaluated pre- and post-intervention. There were increases in the Shoulder MR and LR torque increased for both the dominant (22% and 39%) and non-dominant (36% and 6%) limbs. There was a increase in the Peak and mean forces sustained during maximal handgrip (11% and 7%) and key pinch (280% and 210%) increased in the dominant hand, as well as the shotput (11%) and javelin throw (3%) performance. The tDCS protocol may enhance the upper limb functional performance in a para-athlete with SCI.